Penatalaksanaan Terapi Musik Terhadap Perubahan Intensitas Nyeri Pada Ibu Post Operasi Sectio Caesarea Di Rs Tk II Pelamonia Makassar - Erna Kasim; Andi Tenriola Fitri Kessi; Nirwana (Jurnal Kesehatan Panrita Husada, 2023)
ABSTRACT Introduction: childbirth has become a normal physiological event experienced by every woman. In the process of childbirth, it is not uncommon for women to have problems, so that they do surgery (sectio caesarea). Sectio caesarea surgery will give wounds that will cause pain. One that can reduce the intensity of pain in sectio caesarea mothers is distraction (music therapy). Research objective: to determine the management of music therapy on changes in pain intensity in sectio caesarea mothers. Methods: This study used a descriptive research design using a case study approach to describe (describe) how music therapy is managed on changes in pain intensity in postoperative sectio caesarea mothers. Results: from two respondents, there was a change in pain intensity from a pain scale of 4-6 (moderate pain) decreased from no pain to Mrs "R" and from a pain scale of 7-10 (severe pain) decreased to 1-3 (mild pain ) to Mrs. “K”. Conclusion: music therapy can reduce the intensity of pain in postoperative mothers with sectio caesarea. Keywords: Pain, music therapy, Sectio caesarea